Progress in Stereoselective Construction of C–C Bonds Enabled by Aldolases and Hydroxynitrile Lyases - Liu, Mi; Wei, Dan; Wen, Zexing; Wang, Jian-bo (Frontiers in Bioengineering and Biotechnology, 2021)
The creation of C–C bonds is an effective strategy for constructing complex compounds from simple synthetic blocks. Although many methods have been developed for C–C bond construction, the stereoselective creation of new C–C bonds remains a challenge. The selectivities (enantioselectivity, regioselectivity, and chemoselectivity) of biocatalysts are higher than those of chemical catalysts, therefore biocatalysts are excellent candidates for use in stereoselective C–C bond formation. Here, we summarize progress made in the past 10 years in stereoselective C–C bond formation enabled by two classic types of enzyme, aldolases and hydroxynitrile lyases. The information in this review will enable the development of new routes to the stereoselective construction of C–C bonds.